Antrodia camphorata Increases Insulin Secretion and Protects from Apoptosis in MIN6 Cells - Vong, Chi Teng; Tseng, Hisa Hui Ling; Kwan, Yiu Wa; Lee, Simon Ming-Yuen; Hoi, Maggie Pui Man (Frontiers in Pharmacology, 2016)
Antrodia camphorata (A. camphorata) is a Taiwanese-specific fungus which has been used clinically to treat hypertension, immune- and liver-related diseases and cancer, however it has never been studied in Type II Diabetes (T2DM). Hyperglycaemia in T2DM causes endoplasmic reticulum (ER) stress, leading to β-cell dysfunction. During chronic ER stress, misfolded proteins accumulate and initiate β-cell apoptosis. Moreover, β-cell dysfunction leads to defect in insulin secretion, which is the key process in the development and progression of T2DM. Therefore, the aim of the present study was to examine the effects of A. camphorata on insulin secretion and ER stress-induced apoptosis in a mouse β-cell line, MIN6, and their underlying mechanisms. We demonstrated that the ethanolic extract of A. camphorata increased glucose-induced insulin secretion dose-dependently through peroxisome proliferator-activated receptor-γ (PPAR-γ) pathway, and upregulated genes that were involved in insulin secretion, including PPAR-γ, glucose transporter-2 (GLUT-2) and glucokinase. Furthermore, A. camphorata slightly increased cell proliferation, as well as protected from ER stress-induced apoptosis in MIN6 cells. In conclusion, this study provided evidences that A. camphorata might have anti-diabetic effects and could be a novel drug for T2DM.